Core analysis : a best practice guide - McPhee, Colin; Reed, Jules; Zubizarreta, Izaskun (Elsevier, 2015)
Annotation A practical guide to the design of core analysis programs. Written to address the need for an updated set of recommended practices covering special core analysis and geomechanics tests, the book also provides unique insights into data quality control diagnosis and data utilisation in reservoir models.
Keywords: Drill core analysis -- Handbooks, manuals, etc.; elektronické knihy; electronic books